1976
DOI: 10.1103/physrevlett.37.1348
|View full text |Cite
|
Sign up to set email alerts
|

Reflection and Scattering from CO2-Laser-Generated Plasmas

Abstract: The intensity of 10.6-^m radiation scattered from carbon plasmas has been measured as a function of incidence and collection angles (with angular resolution ^1 0 3°), and of laser mode structure. Over an incident intensity range lO^-lO 13 W cm" 2 , total reflectivity was typically ^>8%. At certain angles, reflectivity often showed 100% temporal modulation. The relevance of these results to critical-surface and stimulated-scattering phenomena is discussed.The reflection and scattering of radiation from laser-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1977
1977
2003
2003

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 19 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…(The higher reflectivity of "4% for longer pulses is in agreement with Baldis and Neufeld 1975, who noted greater reflection of the tail of low-energy TEA laser pulses incident on polyethylene targets.) Of published measurements on total scattered and reflected radiation under comparable experimental conditions, Donaldson et al(1976) observed N 8 % losses from a carbon plasma whilst Stenz et aZ(l977) reported 70% losses from a (CHa)n target.…”
Section: Optical Measurements and Discussion Of Resultsmentioning
confidence: 95%
“…(The higher reflectivity of "4% for longer pulses is in agreement with Baldis and Neufeld 1975, who noted greater reflection of the tail of low-energy TEA laser pulses incident on polyethylene targets.) Of published measurements on total scattered and reflected radiation under comparable experimental conditions, Donaldson et al(1976) observed N 8 % losses from a carbon plasma whilst Stenz et aZ(l977) reported 70% losses from a (CHa)n target.…”
Section: Optical Measurements and Discussion Of Resultsmentioning
confidence: 95%
“…Measured electron temperature as a function of the angle q>9 between the E vector and the incidence plane.…”
mentioning
confidence: 99%